Effects of speed management and roadway parameters on traffic flow along arterials - Suleiman, Ghassan M.; Bezgin, Niyazi Ozgur; Ergun, Murat; Gursoy, Mustafa; Karasahin, Mustafa (ICE PUBLISHING, 2017)
Contemporary traffic engineering relies on effective management of transportation infrastructure to supply the variable mobility demands. Urban arterial congestion is a recurring problem that affects urban traffic flow. The degree of congestion may amplify if the arterial is a principal arterial that leads to a major bridge. Bosporus Bridge, inaugurated in 1973 and renamed in July 2016 as the Martyrs Bridge, is the first of the three suspension bridges connecting the Anatolian and European sides of Istanbul, Turkey. The Martyrs Bridge, along with the recently inaugurated Eurasia Roadway Tunnel provides a direct connection between the southern districts of the Anatolian and European sides of Istanbul for roadway traffic excluding trucks. Recurring congestion observed along the 5.7 km long westbound approach arterial from the Anatolian side of Istanbul to the bridge initiated a study to investigate methods to mitigate congestion through traffic management and improved roadway parameters. A micro simulation model based on traffic data suggested the applicability of traffic speed management along the existing infrastructure to relieve congestion and provide flow stability. The micro simulation model also provided the means for parametric evaluation of the effects of heavy vehicles, lane-width values and interchange spacing on the arterial flow speed and delay.
Keywords: roads & highways; traffic engineering; transport management; Engineering; Transportation